542. A CASE REPORT OF METACHRONOUS CERVICAL ESOPHAGEAL CANCER 7 YEARS AFTER ESOPHAGECTOMY WITH MULTIDISCIPLINARY TREATMENT. (24th September 2022) - Kato, Daiki; Yamada, Kazuhiko; Nohara, Kyoko; Enomoto, Naoki; Yagi, Shusuke; Suyama, Yuto; Aso, Kenta; Akazawa, Naoki; Yokoi, Chizu; Kokudo, Norihiro
Abstract: Background: It is important to check for secondary cancer after esophagectomy. Especially, radiation or chemotherapy for recurrent esophageal cancer, were often performed, and it may be difficult to select treatment for metachronous cancer. We report a case of surgical resection for metachronous cervical esophageal cancer after 7 years for thoracic esophageal cancer with multidisciplinary treatment. Method: A 73-year-old woman underwent right thoracotomy and intrathoracic anastomosis before preoperative chemotherapy for lower thoracic esophageal cancer cT3N3M1 (LN104R) 7 years ago. Final pathological finding was UICC-pT3N3M1 and postoperative additional irradiation was performed. Fifteen months after surgery, there was recurrence of LN112AoP, and definitive chemoradiation therapy was performed. The lesion maintained complete response. Seven years later, upper gastrointestinal endoscopy revealed residual cervical esophageal cancer, and the diagnosis was cT1b (SM) N0M0. Result: Since re-CRT was difficult because of history of irradiation and CRT, we selected surgical cervical esophagectomy without thoracotomy. After partial excision of sternum to widen the view of the upper mediastinum, bilateral laryngeal recurrent nerves were preserved, and trachea and cervical esophagus were exposed. We resected cervical esophagectomy and reconstructed by pedicled jejunum with microvascular anastomosis. The stump of gastric conduit in the thoracic cavity was closed. The final pathology was UICC-pT1bN0M0. Conclusion: There are some cases in which long-term survival can be obtained even for advanced esophageal cancer. It is important to check for secondary cancer after esophagectomy. Radiation therapy and chemotherapy are often used for recurrence of esophageal cancer. We experienced surgical resection for metachronous cervical esophageal cancer 7 years after multidisciplinary treatment for esophageal cancer.